2001
DOI: 10.1590/s0101-81752001000400016
|View full text |Cite
|
Sign up to set email alerts
|

Mudança na dieta da traíra Hoplias malabaricus (Bloch) (Erythrinidae, Characiformes) em lagoas da bacia do rio Doce devido à introdução de peixes piscívoros

Abstract: ABSTRACT. Dict changes of the trahira Hoplias malabariCIIs (Bloch) (Erythrinidac, Characiformes) due to piscivorous introductions in Rio Doce valley lakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
8
0
5
Order By: Relevance
“…This study also found an importance of piscivore fish, with H. malabaricus and A. pantaneiro combined, the second and third largest catches respectively in terms of biomass. The capacity of both to adapt their feeding according to the most abundant prey in the reservoirs (Cantanhede et al, 2008;Pompeu and Godinho, 2001;Novakowski et al, 2007), certainly favored the maintenance of these species under different conditions. Added to the adaptive qualities of the A. pantaneiro, portioned spawning with relatively high fertilization and an absence of parental care (Meurer and Zaniboni-Filho, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found an importance of piscivore fish, with H. malabaricus and A. pantaneiro combined, the second and third largest catches respectively in terms of biomass. The capacity of both to adapt their feeding according to the most abundant prey in the reservoirs (Cantanhede et al, 2008;Pompeu and Godinho, 2001;Novakowski et al, 2007), certainly favored the maintenance of these species under different conditions. Added to the adaptive qualities of the A. pantaneiro, portioned spawning with relatively high fertilization and an absence of parental care (Meurer and Zaniboni-Filho, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This degree of overlap might be related to the opportunistic behavior of these species, given their capacity to change their diet composition according to prey availability or due to biotic interactions, such as competition and predation (Pompeu, Godinho, 2001;Carvalho et al, 2002). In fact, H. mbigua, as other species of Hoplias, presented high feeding plasticity, defined by a varied diet composed of crustaceans, insects, and plants, in addition to a frog (Trachycephalus typhonius -Strictar-Pereira, Oda, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When the tucunaré is introduced into favorable conditions, what may result is the extinction of some autochthonous species through predation (Zaret & Paine, 1973;Godinho & Formagio, 1992;Molina et al, 1996). On the other hand, this threat may be offset by dietary flexibility of endemic tropical piscivores (competitors of the introduced piscivores), which in these environments may be contributing to assure population maintenance (Pompeu & Godinho, 2001). …”
Section: Alimentary Items Popular Namesmentioning
confidence: 99%
“…According to its abundance, it causes modifications in autochthonous fishes populations (Godinho & Formagio, 1992;Fonteles-Filho & Alves, 1995;Pompeu & Godinho, 2001).…”
Section: Introductionmentioning
confidence: 99%